Geography Teacher Candidates' Experiences of Field Study in Western Anatolia: A Qualitative Study - (:unkn) unknown (EDAM, 2012)
The aim of this study is to establish expectations of 5th grade students from. Marmara University's Department of Geography Teaching on geographical held study in Western Anatolia. For this reason, a field study trip was organized to Western Anatolia. A survey, which was consisted of open-ended questions, was prepared by experts and it was conducted on students before and after the study. The survey revealed that 32,2% of the expectations were related to physical geography, 23,1% to human. geography and 44,7% to economic geography. The accumulated data were analyzed using descriptive analysis technique hi conclusion. expectations of students were substantially satisfied after field study. After the fieldwork experience, 67,8% of student expectations were fully met. 7,1% of them were partially met, while 25,1% of their expectations were, not fulfilled, it was also established that the rate of fulfilled expectations related to economic and human geography was higher than those related to physical. geography. The findings were interpreted and suggestions were made concerning the issue.
Keywords: Geographical Field Study; Practical Geography Learning; Student Expectations; Geographic Expedition and Observation